Identification of a Novel Anticancer Oligopeptide from Perilla frutescens (L.) Britt. and Its Enhanced Anticancer Effect by Targeted Nanoparticles In Vitro - Dong-Liang He; Ri-Ya Jin; Hui-Zhen Li; Qing-Ye Liu; Zhi-Jun Zhang (International Journal of Polymer Science)
Objective. Perilla frutescens (L.) Brittis is a dietary herbal medicine and has anticancer effect. However, little is known about its anticancer peptides. This study is aimed at identifying cytotoxic oligopeptides which are loaded by a drug delivery system, to explore its anticancer application. Methods. The oligopeptides were isolated from enzymatic hydrolysates of Perilla seed crude protein by using ultrafiltration, gel filtration chromatography, and reversed-phase high-performance liquid chromatography (RP-HPLC). The structure of the oligopeptide was determined using a peptide sequencer, and its anticancer effect was examined by the MTT assay. PSO (Perilla seed oligopeptide), the most potent anticancer oligopeptide, was loaded by chitosan nanoparticles (NPs) modified by hyaluronic acid (HA). Then, the particle size, zeta potential, encapsulation efficiency (EE), drug loading efficiency (LE), the cumulative release rates of NPs, and its cytotoxic effect on cancer cells were investigated. Results. Three fractions were isolated by the chromatography assay. The third fraction has a broad-spectrum and the strongest anticancer effect. This fraction was further purified and identified as SGPVGLW with a molecular weight of 715 Da and named as PSO. Then, PSO was loaded by HA-conjugated chitosan to prepare HA/PSO/C NPs, which had a uniform size of 216.7 nm, a zeta potential of 35.4 mV, an EE of 38.7%, and an LE of 24.3%. HA/PSO/C NPs had a slow release rate in vitro, with cumulative release reaching to 81.1%. Compared with free PSO, HA/PSO/C NPs showed notably enhanced cytotoxicity and had the strongest potency to human glioma cell line U251. Conclusion. This study demonstrated that PSO, a novel oligopeptide from Perilla seeds, has a broad-spectrum anticancer effect and could be encapsulated by NPs, which enhanced tumor targeting cytotoxicity with obvious controlled release. Our study indicates that Perilla seeds are valuable for anticancer peptide development.